Diagnostic Splenectomy for Visceral Leishmaniasis - Pickering, H (The Royal College of Surgeons of England, 2009)
A 57-year-old-man with a history of malaise, fever,night sweats and shortness of breath presented a diagnostic challenge to his medical team. He was pancytopaenic and had splenomegaly on admission but other investigations, including bone marrow aspiration, proved inconclusive. After the patient deteriorated clinically, the general surgical team was requested to perform a diagnostic splenectomy. The histology of this showed infection with visceral leishmaniasis. He recovered completely with Amphotericin treatment. Although this is a rare condition, particularly for the general surgeon, this case highlights the difficult position surgeons are often put in when performing major surgery diagnostically.